2017
DOI: 10.1086/693043
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Manipulation of Corticosterone Does Not Influence the Clearance Rate of Plasma Testosterone in Birds

Abstract: In vertebrates, exposure to acute stressors stimulates the secretion of adrenal glucocorticoids such as corticosterone, and in some situations this hormone plays an important role in orchestrating the trade-off that exists between reproduction and self-maintenance. Stressful conditions often lead to a decrease in plasma levels of sex steroids such as testosterone in males, and it has been hypothesized that corticosterone contributes to this decrease. Generally supporting this proposition, glucocorticoids can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…In addition, this limited sampling window could have kept us from detecting diminished fat stores following fire (Table 1). Finally, we did not find a relationship between corticosterone and testosterone in our dataset ( Figure S1), thus adding to a growing list of studies in birds suggesting an absence of antagonism between these two hormones (Davies et al 2016, Deviche et al 2017, Abolins-Abols et al 2018.…”
Section: Unornamented Ornamentedsupporting
confidence: 46%
“…In addition, this limited sampling window could have kept us from detecting diminished fat stores following fire (Table 1). Finally, we did not find a relationship between corticosterone and testosterone in our dataset ( Figure S1), thus adding to a growing list of studies in birds suggesting an absence of antagonism between these two hormones (Davies et al 2016, Deviche et al 2017, Abolins-Abols et al 2018.…”
Section: Unornamented Ornamentedsupporting
confidence: 46%
“…This suggests that testes in acutely stressed birds may be less sensitive to downregulation by glucocorticoids, such as corticosterone, but more sensitive to another important hormone -GnIHthat has an inhibitory effect on reproductive physiology (Tsutsui et al, 2010). Indeed, while corticosterone levels increased following the acute handling stressor (Hanauer, 2017), other studies have shown that corticosterone is unlikely to be the cause for rapid decrease in testosterone in response to acute stress in birds (Davies et al, 2016;Deviche et al 2017). Testosterone and corticosterone levels in birds are often either unrelated or positively correlated (Klukowski et al, 1997;Buchanan et al, 2003), showing that corticosterone and testosterone do not covary in a way that is consistent with testosterone suppression by corticosterone.…”
Section: Acute Stressor and Testes Functionmentioning
confidence: 99%
“…Testosterone levels can be suppressed by both psychological (Deviche et al, 2010;Moore and Mason, 2000) as well as physical Nelson et al, 1989) stressors. This decrease may be mediated via suppressive effects of stressors on GnRH or LH secretion (Breen and Karsch, 2006;Breen et al, 2007;Nikolarakis et al, 1986), or by direct action of components of the physiological stress response, such as the hypothalamic-pituitary-adrenal (HPA) axis, on gonads (Deviche et al, 2012(Deviche et al, , 2017Lynn et al, 2015;McGuire et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mitotane is a glucocorticoid synthesis inhibitor that has been shown to consistently reduce baseline 63 [21,22] and stress-induced [22][23][24] corticosterone levels in birds, often to non-detectable levels. We first 64 tested if the effect of mitotane on corticosterone levels in American robins parallels that seen in other 65 species.…”
Section: (B) Treatment Validation 62mentioning
confidence: 99%
“…No. 416855000, dosage 400 mg/kg), following guidelines for the maximum mitotane dosage used in 71 other species [21,22]. Four sham females were injected with a pure peanut oil vehicle (400 µl).…”
Section: (B) Treatment Validation 62mentioning
confidence: 99%